Makna Simbol Bangunan Gereja Inkulturatif Pakpak terhadap Penghayatan Iman dalam Liturgi - Simanjuntak, M. Marihot; Samosir, Yunita Vebry Yanti (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2023)
Humans always use symbols in carrying out their lives as a medium for communicating with the environment, both social and physical. Research on the meaning of the symbols of the Pakpak Inculturative Church Building on the Appreciation of Faith in the Liturgy at Stasi Blessed Dionysius Sumbul was carried out to explain the extent of the people's knowledge about the symbols in the inculturative building and how the inculturative building influences the appreciation of the faith in the liturgy of the people. The method used in this research is a qualitative method with three data collection techniques, namely observation, interviews and documentation. Symbols are interpreted as signs or symbols that contain meaning for understanding the context of beliefs and religions of traditional society. In this research, it was found that the symbols in the Pakpak inculturative church building encouraged the appreciation of the people's faith aesthetically, psychologically and religiously, where it was concluded that the people actually did not fully know the meaning of the symbols in the inculturative church building. However, behind this, people are still able to experience different experiences of faith when worshiping in churches with different models and nuances.